(untitled) (Jurnal Manajemen dan Kewirausahaan, 2007)
This study has something as a purpose to building the empirical models and the new hypothesis between the broad money, surpluses or fiscal deficit, the general price index or inflation rate, demand for monetary base and demand for bank deposit. This study also head for optimal interest rate for bank deposit at the given value of broad money, surplus or fiscal deficit, general price index, demand for monetary base, and demand for bank deposit. The model build consist to balance central bank, intertemporal budget constraint at the maximum expected utility for hold monetary base and bank deposit. The evaluation of the surplus or fiscal deficit stabilization is with the alteration of the requirement reserve ratio, Gross Domestic Product, general price index and interest rate. The results of the study show that the requirement reserve ratio, Gross Domestic Product, general price index and interest rate is very respect to surplus or deficit fiscal. The contribution requirement reserve ratio and interest rate for surplus or deficit fiscal are relatively high. This results show that the clower constraint model can explain the necessary of fiscal and monetary coordinate. Fiscal policy still weak and cause the real business cycle slow down, high inflation and interest rate. The other hands, monetary policy is very strong and cause fiscal surplus is relatively high. The prudent of government and monetary authority are needed to build the fiscal and monetary policy for create the dynamic economy, lower inflation, requirement reserve ratio and interest rate, and the monetary and fiscal dynamic equilibrium. Abstract in Bahasa Indonesia : Studi ini bertujuan membuat model empiris dan hipotesis baru tentang faktor-faktor broad money, surplus dan defisit fiskal, tingkat bunga secara umum, atau tingkat inflasi, permintaan uang primer dan deposito. Selain itu studi ini juga mencari tingkat suku bunga deposito optimal pada nilai tertentu dari faktor-faktor tersebut di atas. Model yang dibangun berhubungan dengan neraca bank sentral, pembatas anggaran intertemporal pada expected utility maksimum, untuk menahan uang primer dan deposito. Evaluasi dari stabilitas surplus dan defisit fiskal diamati dari giro wajib minimum, produk domestik bruto, indeks harga umum, dan tingkat bunga. Hasil studi bahwa giro wajib mnimum, produk domestik bruto, indeks harga umum, dan tingkat bunga berhubungan dengan surplus atau defisit fiskal. Kontribusi dari giro wajib minimum dan tingkat suku bunga terhadap surplus atau defisit fiskal relatif tinggi. Hasil ini menunjukan bahwa clower constraint model dapat menjelaskan perlunya koordinasi antara kebijakan fiskal dan moneter. Kebijakan fiskal masih lemah, dan menyebabkan siklus real bisnis menurun., dan inflasi maupun tingkat bunga yang tinggi. Pada sisi lain terjadinya kebijakan moneter yang sangat kuat menyebabkan surplus fiskal yang relatif tinggi. Evaluasi dar hal ini adalah dibutuhkan oteritas moneter dan pemerintahan yang hati-hati dalam membuat kebijakan moneter dan fiskal, agar tercipta iklim ekonomi yang dinamis, inflasi rendah, giro wajib minimum yang rendah, tingkat bunga yang rendah, serta keseimbangan dinamis antara sektor moneter dan fiskal. Kata kunci:. Surplus dan defisit fiskal, clower constraint model, moneter, fiskal.